„Das sind sie, und das – wir.“ Die Pronomina der belarussischen Protestlyrik 2020–2022 - Wunderwald, Jakob (Wiener Slawistischer Almanach, 2025)
After the 2020 Belarusian presidential elections and during the subsequent protests, poetry was the literary genre most frequently used by Belarusian writers to process the events. This article attempts to map the development of such poetry by examining the works of important Belarusian lyricists written shortly before, during and after the protests. The focus is on the concepts of “I”, “you”, “we” and “they” to be found in the poems. The article seeks answers to questions such as: To what extent does each lyrical “I” project itself as a subject? Is this subject a collective one? Who is its opponent? Does it have friends? – It is postulated that the poems describe how a collective political subject that could only be imagined before the protests, could also be experienced as a concrete reality during the demonstrations. After the protests, this changes again – the new political subject falls into crisis, and poems written in exile express a deep ambivalence concerning the protests. Tracing these processes raises questions about how literature imagines the transformation of 2020, and how this imagination lives on today, even after the protests suffered a political loss.